Garage location selection for residential house by WASPAS-SVNS method - Baušys, Romualdas; Juodagalvienė, Birutė (Journal of Civil Engineering and Management, 2017)
The paper deals with the location selection problem of the garage at the parcel of a single-family residential house. The mathematical model for this real life problem is constructed within MCDM framework. The significance of the chosen criteria was evaluated by AHP approach. The formulated MCDM problem is solved applying WASPAS extension, namely WASPAS-SVNS. The applied single-valued neutrosophic set allows to modeling uncertainty of the initial information explicitly. A numerical example is considered in order to verify the proposed approach.